Interpreting Al-Bughāt and The Ethics of Nation State Citizenship - khoiroh, Muflikhatul; Syakur, Abd (Prodi Hukum Tata Negara Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2022)
This article examines the al-bughāt phenomenon addressed to groups accusing the Indonesian state of being a taghut government. The study garnered primary sources from siyāsah fiqh books discussing al-bughāt. The data collected was analyzed using content analysis, and the results are as follows; al-bughāt is a justified state dissident. The concept of al-bughāt was born within the framework of jināyah fiqh, so it is classified in the ḥudūd criminal provisions. Al-bughāt, in the practical level of early Islamic politics, was in a political frame so that there was no provision for sanctions. Besides, jurists position al-bughāt as the authority of the Islamic state under the political model of the khilāfah, so it is not appropriate when applied in countries that do not adhere to Islamic principles, such as Indonesia. As for certain groups that accuse Indonesia of being a taghut country, they should be more appropriately positioned as deviants who should be facilitated with guidance and counseling. However, if they commit deadly destruction and bombing, they are placed as al-muḥāribūn, whose punishment status is in the al-ḥirābah category. Keywords: al-bughāt, al-ḥudūd, , al-muḥāribūn, jarīmah, ḥadd al-ḥirābah